2021
DOI: 10.1186/s13550-021-00834-2
|View full text |Cite
|
Sign up to set email alerts
|

Imaging modalities for diagnosis and monitoring of cancer cachexia

Abstract: Cachexia, a multifactorial wasting syndrome, is highly prevalent among advanced-stage cancer patients. Unlike weight loss in healthy humans, the progressive loss of body weight in cancer cachexia primarily implicates lean body mass, caused by an aberrant metabolism and systemic inflammation. This may lead to disease aggravation, poorer quality of life, and increased mortality. Timely detection is, therefore, crucial, as is the careful monitoring of cancer progression, in an effort to improve management, facili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 139 publications
1
27
0
1
Order By: Relevance
“…This might be particularly relevant within the context of cancer-associated weight loss and cachexia, as escalated glucose consumption by tumors can distort systemic metabolic flux and suggest increasingly malignant genetic dysregulation through mechanisms such as the Warburg effect. Our research team previously demonstrated the relevance of 18 F-FDG uptake in incidence of significant pretreatment weight loss and survival for patients with gastroesophageal cancer (17). Prior studies have supported alternate uses of PET imaging for the detection of cancer cachexia (18), linking low hepatic uptake (19) and increased metabolically active brown adipose tissue uptake (20) of 18 F-FDG with the syndrome.…”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…This might be particularly relevant within the context of cancer-associated weight loss and cachexia, as escalated glucose consumption by tumors can distort systemic metabolic flux and suggest increasingly malignant genetic dysregulation through mechanisms such as the Warburg effect. Our research team previously demonstrated the relevance of 18 F-FDG uptake in incidence of significant pretreatment weight loss and survival for patients with gastroesophageal cancer (17). Prior studies have supported alternate uses of PET imaging for the detection of cancer cachexia (18), linking low hepatic uptake (19) and increased metabolically active brown adipose tissue uptake (20) of 18 F-FDG with the syndrome.…”
Section: Introductionmentioning
confidence: 95%
“…Our research team previously demonstrated the relevance of 18 F-FDG uptake in incidence of significant pretreatment weight loss and survival for patients with gastroesophageal cancer (17). Prior studies have supported alternate uses of PET imaging for the detection of cancer cachexia (18), linking low hepatic uptake (19) and increased metabolically active brown adipose tissue uptake (20) of 18 F-FDG with the syndrome.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations